Mortal - Dekker, Ted, 1962- (Dekker, Ted, 1962- Books of mortals., 2012)
Rom Sebastian discovered a secret and consumed an ancient potion of blood to bring himself back to life. Nine years later, surviving against impossible odds, he has gathered a secret faction of followers who have also taken the blood--the first Mortals in a world that is dead. But the Order has raised an elite army to hunt and crush the living, and no one knows the path to survival.